Identifikasi dan Prevalensi Telur Cacing Parasit pada Feses Sapi (Bos sp.) yang Digembalakan di Tempat Pembuangan Akhir Sampah (TPAS) Tamangapa Makassar - Cut Muthiadin; Isna Rasdianah Aziz; Firdayana Firdayana (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
Grazing the cows not only on the grass, but today there are at landfill. This study aimed to determine the type of parasitic worms in cow feces and to determine the prevalence of worm eggs in the feces of cattle in pastored around the landfill Tamangapa Makassar. Identification qualitatively using flotation method, whereas quantitative using Mc. Master method. The identification results obtained from 25 samples of cow feces, there are 3 types of positive samples containing worm eggs Oesophagostomum sp. and Cooperia sp. using the floating method. While using Mc. Master method showed nothing of the worm eggs.